DEVELOPING A DIGITAL PICTURE BOOK FOR SPEAKING COMPETENCE - Safriyani Novitri Yani; Estika Satriani; Wilda Srihastuty Handayani Piliang (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to prepare a new product in the process of learning English, especially for semester 1 students. The product to be prepared is a digital picture book-based learning medium (e-book). Digital picture books (e-books) are made specifically to guide students to become more skilled in learning English according to ethical norms and customary values. Digital picture books or e-books will be packaged more independently and can be used directly by students with the help of the teacher or personally. This research uses the development method by adapting the IDI model, which has three stages of development: planning, design, and development. All processes will be adjusted based on the students' needs in terms of English skills. Quantitative data were collected through questionnaires and testing, and qualitative data were collected through interviews. To develop learning materials to offer students, researchers sought to find needs analysis, effectiveness, and practicality of the products in designing and implementing. Based on the research findings, the study was considered valid and practical and could be used to improve the quality of English comprehension among students.